The Association between Stimulant, Opioid, and Multiple Drug Use on Behavioral Healthcare Utilization in a Safety-Net Health System - Calcaterra, Susan L (Subst Abus, 2015)
BACKGROUND: Prior studies show an association between drug use and healthcare utilization. The relationship between specific drug type and emergent/urgent, inpatient, outpatient and behavioral healthcare utilization has not been examined. We aimed to determine if multiple drug use was associated with increased utilization of behavioral healthcare. METHODS: To assess healthcare utilization, we conducted a retrospective cohort study of patients who accessed healthcare at a safety-net medical center and affiliated clinics. Using electronic health records, we categorized patients who used stimulants, opioids, or multiple drugs based on urine toxicology screening tests and/or International Classification of Diseases, 9(th) Revision (ICD-9). Remaining patients were categorized as patients without identified drug use. Healthcare utilization by drug use group and visit type was determined using a negative binomial regression model. Associations were reported as incidence rate ratios. Utilization was described by rates of healthcare-related visits for inpatient, emergent/urgent, outpatient, and behavioral healthcare among patients who used drugs, categorized by drug types, compared to patients without identified drug use. RESULTS: Of 95,198 index visits, 4.6% (n=4,340) were by patients who used drugs. Opioid and multiple drug users had significantly higher rates of behavioral healthcare visits than patients without identified drug use (opioid incidence rate ratio [IRR]=7.2; 95% confidence interval [CI] 3.8–13.8; multiple drug use IRR=5.6, 95% CI 3.3–9.7). Patients who used stimulants were less likely to use behavioral health services (IRR=1.3, 95% CI 0.9–2.0) when compared to opioid and multiple drug users, but were more likely to use inpatient (IRR=1.6, 95% CI 1.4–1.8) and emergent/urgent care (IRR=1.4, 95% CI 1.3–1.5) services as compared to patients without identified drug use. CONCLUSIONS: Integrated medical and mental healthcare and drug treatment may reduce utilization of costly healthcare services and improve patient outcomes. How to capture and deliver primary care and behavioral healthcare to patients who use stimulants needs further investigation.